Pertanggungjawaban Pidana Bagi Pelaku Penyalahgunaan Airsoft Gun: Studi Putusan Pengadilan Negeri Simalungun - Panji Nugraha; Madiasa Ablisar; Mahmud Mulyadi; Chairul Bariah (Universitas Sumatera Utara, 2019)
Abtracts. Airsoft gun that in principle is used with a positive purpose, but in reality there are only among the people who abuse sports firearms is not as it should be. This misuse can certainly be detrimental to others because if this type of airsoft gun is not used in accordance with applicable procedures, it can be functionally used as a dangerous firearm and can injure the target and even threaten the life of the person being the target of the shot. Along with the complexity of economic problems that continue to squeeze most of the community lately, crime rates are also growing more and more rampant from day to day, often even perpetrators of crimes have used firearms in every crime, and some of these criminals use airsoft guns as a tool to threaten victims. The issues raised in this study, namely how the legal regulation of criminal acts of misuse of airsoft gun in the environment of civil society, the consideration of judges in the simalungun district court ruling that equates airsoft guns with firearms and criminal liability for perpetrators of misuse of airsoft gun misuse in court decisions simalungun country. To find answers to these problems, this research uses descriptive analytical normative legal research, in which normative legal research uses secondary data as the main data using data collection techniques carried out by library research, and data analysis uses qualitative data analysis methods. Keywords: crime, misuse, airsoft gun.